(untitled) (Latakia University Journal -Medical Sciences Series, 2019)
يهدف هذا البحث إلى دراسة ثبات المسافة بين الأنياب لحالات سوء الإطباق من الصنف الأول المعالجة تقويمياً بقلع أو بدون قلع . أجري هذا البحث على عينة مكونة من (116) حالة سوء إطباق من الصنف الأول منهم (50) مريضاً (31 أنثى , 19ذكراً) تم علاجهم تقويمياً بعد قلع ضواحك من الفكين العلوي والسفلي ، و(66) مريضاً (45إناث , 21 ذكور) تم علاجهم بدون قلع ضواحك،تراوحت أعمارهم (12-27) سنة تم انتقاؤهم من المرضى المراجعين لوحدة تقويم الأسنان في كلية طب الأسنان بجامعة تشرين . إذ تم إجراء تحليل قياسي للمسافة بين الأنياب على الأمثلة الجبسية لجميع أفراد العينة بالتعاقب قبل المعالجة التقويمية النشطة (ICD1) وبعد انتهاء المعالجة النشطة (ICD2) وبعد 7 سنوات من نهاية التثبيت (ICD3) . أظهرت نتائج هذه الدراسة زيادة في قيمة المسافة بين الأنياب تزداد في مرحلة المعالجة وانخفاضاً في قيمة المسافة بين الأنياب في الفترة التالية للتثبيت سواء أكان العلاج التقويمي بقلع ضواحك أم بدون قلع . ويستنتج أيضاً من هذه الدراسة أن المسافة بين الانياب العلوية أكثر ثباتاً من مثيلاتها السفلية بعد المعالجة التقويمية . The Purpose of this study is to determine the stability of inter-canine distance in class I malocclusion cases treated with or without extraction. The sample consists of 116 patients (aged 12-27 years) with class I malocclusion. 50 patients (31 females, 19 males) are treated with extraction of premolars from the upper and lower arches. 66 patients (45 females, 21 males) are treated without extraction of premolars. Those patients have been selected from the Orthodontic Unit in the Faculty of Dentistry at Tishreen University. A measurement analysis was carried out for inter-canine distance on plaster models for whole study sample before active treatment (ICD1), after active treatment (ICD2), and, as well, 7 years post retention (ICD3). Results have showed an increase of inter-canine distance in treatment phase, and reduction of inter-canine distance following retention, whether the treatment was achieved with or without premolars extraction. Results also showed that inter-canine distance was more stable in the upper arch than in the lower arch after orthodontic treatment.